2020
DOI: 10.1292/jvms.19-0566
|View full text |Cite
|
Sign up to set email alerts
|

Identification and pathogenicity analysis of <i>Streptococcus equinus</i> FMD1, a beta-hemolytic strain isolated from forest musk deer lung

Abstract: Streptococcus spp. cause a wide range of diseases in animals and humans. A Streptococcus strain (FMD1) was isolated from forest musk deer lung. To identify the bacterium at the species level and investigate its pathogenicity, whole genome sequencing and experimental infections of mice were performed. The genome had 97.63% average nucleotide identity with the S. equinus strain. Through virulence gene analysis, a beta-hemolysin/cytolysin genome island was found in the FMD1 genome, which contained 12 beta-hemolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Pulmonary fibrosis is the final stage of many lung diseases in humans, which have also been described in dogs, cats, horses and FMD ( Zhang, Wang & Lin, 1997 ; Zhao et al, 2020 ; Williams, 2014 ; Marenzoni et al, 2011 ). In this study, five FMD were found suffering from BIPF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary fibrosis is the final stage of many lung diseases in humans, which have also been described in dogs, cats, horses and FMD ( Zhang, Wang & Lin, 1997 ; Zhao et al, 2020 ; Williams, 2014 ; Marenzoni et al, 2011 ). In this study, five FMD were found suffering from BIPF.…”
Section: Discussionmentioning
confidence: 99%
“…The population of captive FMD has been hampered by bacterial pneumonia, which accounts for 50% of all deaths. Specifically, pulmonary fibrosis has been presented in almost all of the bacterial pneumonia FMD ( Zhang, Wang & Lin, 1997 ; Zhao et al, 2020 ). Pulmonary fibrosis is one of the respiratory refractory diseases affecting human and animal health ( Williams, 2014 ), which is a progressive fatal disease accompanied by the inflammatory response, excessive proliferation of fibroblast cell, and deposition of extracellular matrix (ECM) ( Williams, 2014 ; Hsu et al, 2017 ; Wang et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the β‐h/c‐dependent β‐hemolysis in S. agalactiae , a nonhemolytic strain with the disruption of cylA gene by IS1381A insertion and a frameshift mutation in cylE gene was reported recently 34 . In addition, although β‐h/c is generally specific for S. agalactiae , it was also recently reported that the cyl operon composed of 12 ORFs was found in the genome of S. equinus FMD1 35 …”
Section: Distribution Of β‐Hemolysin‐encoding Gene In Streptococcimentioning
confidence: 99%
“…The forest musk deer (Moschus berezovskii) is a medium-sized mammal found in alpine forests (Zhao et al, 2011;Zhao et al, 2020a). This deer (Moschus spp.)…”
Section: Introductionmentioning
confidence: 99%